2002
DOI: 10.1038/sj.bmt.1703615
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modulation of glutathione cellular content on busulphan-induced cytotoxicity on hematopoietic cells in vitro and in vivo

Abstract: Summary:Busulphan is used in conditioning regimens prior to SCT. A relationship between exposure to busulphan, expressed as an area under the plasma concentration time curve (AUC), and effect and/or adverse effects, such as veno-occlusive disease (VOD), was reported. Exhaustion of glutathione (GSH) contributes to VOD and modulation of intracellular levels of GSH influences bulsulphan-induced toxicity in hepatocytes. Thus, increase of GSH might serve as prophylaxis against VOD. However, it should not interfere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…30,31 Thus the lack of donor alloreactivity against host residual cells and/or the high dose of BU may explain the lack of need of CY. In our previous studies, 32,33 we have shown that similar myeloablative effects of BU were obtained after the administration of BU as i.v. or i.p., therefore, BU was administered i.p.…”
Section: Discussionmentioning
confidence: 88%
“…30,31 Thus the lack of donor alloreactivity against host residual cells and/or the high dose of BU may explain the lack of need of CY. In our previous studies, 32,33 we have shown that similar myeloablative effects of BU were obtained after the administration of BU as i.v. or i.p., therefore, BU was administered i.p.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown that the major route of BU metabolism is through GSH-S-transferase catalyzed conjugation to GSH [18,19]. Therefore, treatment of cells with BU can lead to GSH depletion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ROS can function as a signal molecule to stimulate the Erk-p38 MAPK pathway [17]. BU has the ability to increase ROS production in part by depletion of intracellular GSH [18,19]. Therefore, we hypothesized that BU may activate Erk and p38 by inducing oxidative stress.…”
Section: Bu Induces a Transient Reduction In Gsh But A Continuous Incmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, hepatocytes would be more susceptible to injury caused by other drugs following BU administration. 38 Indirect evidence supporting this hypothesis comes from the studies suggesting a lower risk of sinusoidal injury when BU is given last in order in the BU/CY regimen. 39 Several strategies have been developed in an attempt to reduce the impact of liver dysfunction on mortality after SCT, including the use of danaparoid, defibrotide and N-acetylcysteine.…”
Section: Discussionmentioning
confidence: 96%